The impact of playing tennis on the organ of vision - threats, benefits and prevention of the organ of vision - Rabstein, Dominik; Gościniewicz, Piotr; Porwolik, Hanna; Porwolik, Agata; Pabis, Patrycja; Porwolik, Agnieszka; Bodera, Magdalena; Szydłowski, Radosław (Journal of Education, Health and Sport, 2025)
This paper examines the impact of playing tennis on the visual system, providing an in-depth analysis of physiological, adaptive, and risk-related aspects associated with the sport. The dynamic nature of tennis necessitates intensive visual engagement to track a fast-moving ball, thereby enhancing dynamic vision, depth perception, and visuomotor coordination. On the other hand, the sport also poses risks such as eye strain and mechanical injuries, including corneal and retinal damage. The study underscores the importance of peripheral vision in the game and the need for the visual system to adapt to varying lighting conditions. The authors highlight the benefits of implementing vision exercises and protective measures, such as sunglasses and contact lenses. The significance of preventive measures, regular eye check-ups, and education for players, coaches, and parents is also emphasized. Although demanding, tennis offers opportunities to improve visual functions, contributing to athletic development and visual health.